Makna Kontekstual Tokoh Uta dalam Teks Terjemahan Bahasa Indonesia pada Film One Piece Film: Red - Firman Saputra; Indah Fajarini; Tanita Liasna (Medan Resource Center, 2026)
This study investigates the contextual meanings conveyed through Uta's utterances in the Indonesian subtitle translation of One Piece Film: Red to examine how contextual elements shape meaning and how effectively these meanings are retained in audiovisual translation. The research addresses the question of whether the Indonesian subtitles successfully preserve the contextual meanings, communicative intentions, and emotional nuances embedded in the source language despite the linguistic and technical constraints of subtitling. A descriptive qualitative approach was employed by analyzing Uta's translated utterances, which were classified into seven contextual dimensions: participants, situation, communicative purpose, emotional state, time, place, and topic of discussion. The analysis identified 66 contextual meaning instances, with emotional context emerging as the most dominant category, indicating that emotional expression constitutes the central semantic feature of Uta's dialogue. The findings further demonstrate that the Indonesian subtitles generally maintain the intended contextual meanings and communicative functions of the original utterances, although certain lexical simplifications occur to accommodate subtitle limitations. These results underscore that a comprehensive understanding of contextual meaning is essential for producing accurate, natural, and communicatively effective subtitle translations in audiovisual media.